Age-Related Regeneration of Osteochondral and Tibial Defects by a Fibrin-Based Construct in vivo - Feng, Xue; Xu, Peifang; Shen, Tao; Zhang, Yihan; Ye, Juan; Gao, Changyou (Frontiers in Bioengineering and Biotechnology, 2020)
A fibrin gel filled macroporous fibrin scaffold (fibrin-based scaffold) was fabricated by loading fibrinogen via a negative pressure method, following with thrombin crosslinking. The macroporous fibrin scaffold exhibited porous structure with porosity of (88.1±1.3)% and achieved a modulus of 19.8±0.4 kPa at a wet state after fibrin gel filling, providing a suitable microenvironment for bone marrow-derived mesenchymal stem cells (BMSCs). The fibrin-based scaffolds were then combined with BMSCs and lipofectamine/pDNA-TGF-β1 complexes to obtain the fibrin-based constructs, which were implanted into osteochondral and tibial defects at young and aged adult rabbits, respectively. Partial repair of osteochondral defects and perfect restoration of tibial defects were realized at 18 w post-surgery for the young adult rabbits, whereas only partial repair of subchondral bone and tibial bone defects were found at the same time for the aged adult rabbits, confirming the adaptability of the fibrin-based constructs to the different tissue microenvironments by tissue-biomaterial interplays.